2019
DOI: 10.1007/5584_2019_428
|View full text |Cite
|
Sign up to set email alerts
|

Quinolines and Quinolones as Antibacterial, Antifungal, Anti-virulence, Antiviral and Anti-parasitic Agents

Abstract: Infective diseases have become health threat of a global proportion due to appearance and spread of microorganisms resistant to majority of therapeutics currently used for their treatment. Therefore, there is a constant need for development of new antimicrobial agents, as well as novel therapeutic strategies. Quinolines and quinolones, isolated from plants, animals, and microorganisms, have demonstrated numerous biological activities such as antimicrobial, insecticidal, antiinflammatory, antiplatelet, and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 136 publications
(137 reference statements)
0
54
0
Order By: Relevance
“…Recently, chloroquine has also been used to treat COVID-19 (50). Broad-spectrum activities have also been reported for other classes of pharmacological drugs (51), indicating that drug repurposing represents a fertile reservoir to develop drugs to fight COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chloroquine has also been used to treat COVID-19 (50). Broad-spectrum activities have also been reported for other classes of pharmacological drugs (51), indicating that drug repurposing represents a fertile reservoir to develop drugs to fight COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Quinoline derivatives have many diverse applications as anti-malarial, anti-viral, anti-bacterial, anti-asthmatic, etc., agents [ 5 , 6 ]. In addition, quinoline scaffold and several quinoline analogs have been reported as anti-cancer agents with promising anti-proliferative activity against multiple cancer cell lines, including HeLa (cervical cancer cell line) and MDA-MB-435 (melanoma) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoline and its derivatives have always attracted both synthetic and biological chemist because of its diverse chemical and pharmacological properties [1] , [2] , [3] , [4] , [5] , [6] . Literature survey revealed that quinoline derivatives had shown potency as antiviral agents against several viruses such as human immunodeficiency virus, Zika virus, H1N1 influenza virus, Hepatitis C virus, dengue virus, vaccinia virus and respiratory syncytial virus [7] , [8] , [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%